(untitled) (Research, Society and Development, 2025)
Leprosy, also known as Hansen’s disease, is an infectious and contagious disease caused by Mycobacterium leprae, an obligate intracellular parasite with affinity for skin cells and peripheral nerves. It is a chronic condition with a high potential for disabling lesions, reflecting the socioeconomic level of the affected countries. The global response to the COVID-19 pandemic required a reorganization of health services to address the public health emergency, which resulted in the postponement of regular outpatient care, thereby affecting the diagnosis and treatment of several diseases, including leprosy. This study aimed to analyze the impact of these changes on the diagnosis and management of leprosy in the municipality of Cascavel, Paraná State, observing a significant reduction in new cases and an increase in recurrences during and after the pandemic. These findings suggest underreporting due to limited access to health services. The study highlights the importance of strengthening surveillance and contact tracing, as well as implementing strategies to ensure continuity of care even in times of health crises, in order to minimize the impact on chronic diseases such as leprosy.